High stretchable and self-healing nanocellulose-poly(acrylic acid) composite hydrogels for sustainable CO2 shutoff - Liu, Ziteng; Wei, Peng; Qi, Ying; Huang, Xueli; Xie, Yahong (Carbohydrate polymers, 2023)
The injection of CO2 into oil reservoirs to enhance oil recovery (EOR) has become a widely accepted and effective technical method, which, however, remains subject to the gas channeling caused by the reservoir fractures. Herein, this work developed a novel plugging gel combining excellent mechanical properties, fatigue resistance, elastic and self-healing properties for the CO2 shutoff purpose. This gel consisting of grafted nanocellulose and polymer network was synthesized via a free-radical polymerization, and reinforced by using Fe3+ to cross-link the two networks. The as-prepared PAA-TOCNF-Fe3+ gel has a stress of 1.03 MPa and a high strain of 1491 %, and self-heals to its original 98 % in stress and 96 % in strain after rupture, respectively. The introduce of TOCNF/Fe3+ improves the excellent energy dissipation and self-healing via the synergy effect of dynamical coordination bonds and hydrogen bonds. Further, the PAA-TOCNF-Fe3+ gel is both flexible and high-strength in plugging the multi-round CO2 injection, during which the CO2 breakthrough pressure is above 9.9 MPa/m, the plugging efficiency exceeds 96 %, and the self-healing rate is larger than 90 %. Given that above, this gel shows a great potential to plug the high-pressure CO2 flow, which could offer a new method for CO2-EOR and carbon storage. [Display omitted]